Rifampicin Does not Significantly Affect the Expression of Small Heterodimer Partner in Primary Human Hepatocytes - Pavek, Petr; Stejskalova, Lucie; Krausova, Lucie; Bitman, Michal; Vrzal, Radim (Frontiers in Pharmacology, 2012)
The small/short heterodimer partner (SHP, NR0B2) is a nuclear receptor corepressor lacking a DNA binding domain. SHP is induced by bile acid-activated farnesoid X receptor (FXR) resulting in CYP7A1 gene suppression. In contrast, Pregnane X receptor (PXR) activation by its ligands was recently suggested to inhibit SHP gene transactivation to maximize the induction of PXR target genes. However, there are also conflicting reports in literature whether PXR or rodent Pxr activation down-regulates SHP/Shp expression. Moreover, the PXR-mediated regulation of the SHP gene has been studied only at the SHP mRNA and transactivation (gene reporter assay) levels. In this study, we studied the effect of rifampicin, a prototype PXR ligand, on SHP mRNA and protein expression in three primary human hepatocyte cultures. We found that SHP mRNA is not systematically down-regulated in hepatocyte in culture after 24 h treatment with rifampicin. Consistently, we did not observe down-regulation of SHP protein in primary human hepatocytes after 24 and 48 h of incubation with rifampicin. We can conclude that although we observed slight down-regulation of SHP mRNA and protein in several hepatocyte preparations, the phenomenon is unlikely critical for PXR-mediated induction of its target genes.